Cellular functions and mechanisms of action of small heat shock proteins - Mogk, Axel; Ruger-Herreros, Carmen; Bukau, Bernd (Annual review of microbiology, 2019)
Small heat shock proteins (sHsps) constitute a diverse chaperone family that shares the α-crystallin domain, which is flanked by variable, disordered N- and C-terminal extensions. sHsps act as the first line of cellular defense against protein unfolding stress. They form dynamic, large oligomers that represent inactive storage forms. Stress conditions cause a rapid increase in cellular sHsp levels and trigger conformational rearrangements, resulting in exposure of substrate-binding sites and sHsp activation. sHsps bind to early-unfolding intermediates of misfolding proteins in an ATP-independent manner and sequester them in sHsp/substrate complexes. Sequestration protects substrates from further uncontrolled aggregation and facilitates their refolding by ATP-dependent Hsp70-Hsp100 disaggregases. Some sHsps with particularly strong sequestrase activity, such as yeast Hsp42, are critical factors for forming large, microscopically visible deposition sites of misfolded proteins in vivo. These sites are organizing centers for triaging substrates to distinct quality control pathways, preferentially Hsp70-dependent refolding and selective autophagy.
Gesehen am 22.10.2019